Index Based Livestock Takaful e-learning course introduction - Bashir, H. (International Livestock Research Institute, 2016)
An introduction of the Index Based Livestock Takaful (IBLT) e-learning course by Hassan Bashir, CEO of Takaful Insurance of Africa.